Looking at The Civil Suits and Court Cases Under the Justice Against Sponsors of Terrorism Act: Why it Fails? - Ali Ibrahim Alheji; Shahrul Mizan Ismail (Faculty of Law, Sriwijaya University, Indonesia, 2025)
Terrorism remains a persistent and significant global threat, with far-reaching consequences for world peace and stability. The September 11, 2001 attacks marked a pivotal moment in the fight against terrorism, prompting governments and international organizations to adopt new strategies to counter this threat. In response to these tragic events, the United States enacted the Justice Against Sponsors of Terrorism Act (JASTA), a legislative framework designed to allow victims of terrorism to seek compensation from state sponsors of terrorism. While JASTA reflects a commitment to holding individuals and nations accountable for supporting terrorism, it has sparked controversy, with critics arguing that it undermines the principle of sovereign immunity, while others view it as a crucial tool for combating terrorism. This study examines the legal and procedural implications of JASTA, focusing on the challenges of bringing civil actions under this law. Through a literature-based research approach, the study explores anti-terrorism laws, relevant case law, and the practical obstacles of pursuing legal claims under JASTA. The findings highlight the legal complexities and political considerations involved in holding state sponsors accountable, emphasizing the need for a balanced approach that upholds international law and diplomacy while ensuring justice for terrorism victims. This research contributes to ongoing discussions on refining strategies to combat state-sponsored terrorism and offers recommendations for potential legislative reforms to enhance the effectiveness of JASTA in achieving justice.